Effectiveness of Grade 1 and 2 Joint Mobilizations with Non Steroidal Anti Inflammatory Drugs (NSAIDS) in Comparison with NSAIDS alone in Pain Management of Knee Osteoarthritis - Salman Akram, Murtaza Gondal, Sumera Mushtaq, Uzma Rafiq, Furqan Ahmad, Mohammad Arshad (Journal of Rawalpindi Medical College, 2017)
To analyze the effectiveness of Grade 1 and 2 joint mobilizations with NSAIDS in comparison with NSAIDS alone in pain management of knee osteoarthritis. Methods: In this randomized controlled trial patients with knee osteoarthritis (n=50) were divided into two groups, 25 patients in each group. Control group received diclofenac salt 50mg in twice daily dose along with quadriceps and knee joint exercises, while experimental group received knee joint mobilizations grade 1 and 2 in addition to the diclofenac salt 50mg twice daily dose and quadriceps and knee joint exercises. Main outcome was moderate, good or excellent control of pain with the intervention. Among secondary parameters were the effect on pain intensity, quality of life, and functionality.Grades of mobilizations used are defined as per Kaltenborn. Results: At the end of six weeks the knee pain with activities improved in the experimental group (mean7.44) compared to control group (mean 11.28) and pain with physical function also showed improvement in experimental (mean 25.84) as compared to control (mean 36.28). The stiffness also showed better mean values in the experimental (mean 2.08) to control (Mean 3.12). Visual analog scale readings also showed improvement in experimental group (mean 5.12) compared to control (mean 6.84). Conclusions: Grade 1 and 2 manual knee joint mobilizations in combination with diclofenac salt are more effective than diclofenac salt alone. Emphasis of this therapy should be given to reduce knee joint pain, stiffness and improvement in physical function on various activities.